Culturally Safe Nursing: Transformative Learning Experiences Through Critical Reflection Assessment - Lesley Andrew; Michelle Pedlow; Bev Ewens (Nursing Open, 2026)
ABSTRACT Aim To explore the transformative learning experiences of postgraduate nursing students engaging in an Aboriginal culture and history module, through an analysis of a critical reflection assessment, in particular the student development of cultural awareness and culturally safe practice. Background Despite mandated inclusion of Aboriginal cultural content in Australian nursing curricula, culturally unsafe practices and racism persist. Transformative learning, underpinned by critical reflection, can challenge fixed assumptions and promote cultural awareness and culturally safe care. Design A qualitative descriptive study using thematic analysis. Methods Written critical reflections from 15 consenting postgraduate nursing students who completed the Ngany Kalyakal Katatjiny Boordawan Module, which was developed to promote culturally safe care of Australian nurses, were analysed using Braun and Clarke's thematic analysis and interpreted through Tsimane and Downing's conceptual model of transformative learning. Results The three developed themes were: (1) Students' initial awareness and understanding of Aboriginal culture, history and health—revealing knowledge gaps and societal influences; (2) The learning experience—characterised by emotional responses, identification with Aboriginal experiences and critical re‐examination of traditional healthcare perspectives; and (3) Practice through a new lens—demonstrating conceptual shifts and intentions to apply culturally safe approaches in practice. Conclusion Critical reflection of culture and health learning activities can support transformative learning, challenge prior assumptions and facilitate the development of skills and attitudes aligned with culturally safe nursing practice. Careful planning of these learning activities is needed to manage student emotional discomfort. Impact Findings highlight the need for authentic, meaningful reflective activities and ongoing evaluation of cultural and health education across nursing curricula. Implications for Nursing Practice The findings highlight the importance of integrating authentic, meaningful learning experiences into nursing curricula, including reflective assessment strategies that foster transformative learning and equip future nurses to provide culturally safe care.